PEMAHAMAN KEBERAGAMAAN DAN GERAKAN KELOMPOK FPI SURABAYA - Maâ€™arif, Syamsul (Jurnal THEOLOGIA, 2012)
Attitudes ofÂ FPIÂ (Islamic Defenders Front) inÂ IndonesiaÂ so far Â impressed 'frontal' and againstÂ any form ofÂ indecent behavior.Â Their action, in factÂ it can be saidÂ as one of theÂ deepestÂ expressionÂ ofÂ a group ofÂ MuslimsÂ in articulatingÂ religious teachingsÂ areÂ embraced, or as an attitude of "piety" in viewing ofÂ allÂ the different faithsÂ in the beliefÂ that he believes. EspeciallyÂ in view ofÂ problemsÂ that are clearlyÂ regardedÂ as a form ofÂ disobedience, apostasyÂ andÂ blasphemy.Â The responsesÂ and reactions, as well asÂ research that has beenÂ conducted by the authorÂ inÂ SurabayaÂ is in order toÂ uphold theÂ principles ofÂ faithÂ areÂ considered "correct" earlier. This paper aimsÂ toÂ provideÂ comprehensive information onÂ what factorsÂ underlieÂ the birth ofÂ contemporaryÂ religiousÂ groups-particularly FPIÂ inÂ Surabaya. And find theÂ religious understanding, activityÂ and movementsÂ FPIÂ groupÂ in the area.Â Overview ofÂ the resultsÂ of this studyÂ are expected toÂ eventuallyÂ be able toÂ eliminateÂ the possibility ofÂ misunderstandingÂ informationÂ is the cause ofÂ the onset ofÂ prejudiceÂ andÂ stereotypesÂ is the first stepÂ in conflict orÂ resolveÂ conflicts betweenÂ religiousÂ communitiesÂ in a comprehensive manner. Therefore, theÂ knownÂ diversity ofÂ religious groupsÂ with the dynamics ofÂ movements willÂ make it easier forÂ religiousÂ communitiesÂ toÂ learn from eachÂ other.Â Sikap-sikap FPI (Front Pembela Islam) di Indonesia selama ini terkesan â€˜frontalâ€™ dan melawan setiap bentuk kemunkaran. Aksi mereka, sebenarnya bisa dikatakan sebagai salah satu bentuk ekspresi terdalam dari sekelompok orang muslim dalam mengartikulasikan ajaran-ajaran agama yang dipeluknya, atau sebagai bentuk sikap â€œkesalehanâ€ dalam memandang setiap keyakinan yang berbeda dengan keyakinan yang diyakininya. Apalagi dalam memandang persoalan yang jelas-jelas dianggap sebagai bentuk kemaksiatan, kesesatan dan penodaan agama. Maka respons dan reaksi mereka, sebagaimana hasil penelitian yang telah dilakukan penulis di Surabaya adalah dalam rangka menegakkan prinsip keimanan yang dianggap â€œbenarâ€ tadi. Tulisan ini bertujuan untuk memberikan informasi yang komprehensif tentang faktor apa saja yang melatari lahirnya kelompok-kelompok keagamaan kontemporerâ€”terutama sekali FPI di Surabaya. Sekaligus mengetahui pemahaman keagamaan, aktifitas dan gerakan-gerakan kelompok FPI di daerah tersebut. Gambaran hasil penelitian ini pada akhirnya diharapkan mampu mengeliminasi kemungkinan kesalahpahaman informasi yang menjadi sebab timbulnya prejudice, dan stereotype yang merupakan langkah awal terjadinya konflik atau mengatasi konflik antar komunitas agama secara komprehensif. Sebab, dengan diketahui keanekaragaman kelompok-kelompok keagamaan denganÂ dinamika gerakannya Â akan lebih memudahkan masyarakat agama untuk saling belajar satu sama lain.